Microfacies and Sedimentary environment of Aliji Formation in selected wells from Kirkuk oil fields north Iraq - Lafta S. Kadhim; Faris N.Hassan; Tay H. Mansour (Tikrit Journal of Pure Science)
The study carried out of Aliji Formation (Late Paleocene) for selected wells in three oil fields Kirkuk, Bai Hassan and Jambur The thickness of formations in the studied wells area (K-229) 172m, (BH-96) 57m,and (JM-55) 52m.